The human dopaminergic system: cerebral SPECT - Valença, Marcelo Moraes; Bem Junior, Luiz Severo; Silva, Ana Cristina Veiga; Andrade-Valença, Luciana Patrízia Alves (Avanços em Medicina, 2025)
Image in Medicine